Effect of abdominal paracentesis drainage on TLR4 expression in liver of rats with early severe acute pancreatitis - CHEN Zhen-yu, HUANG Qi-lin, SUN Hong-yu, LIU Li-ye, WEN Yi (Jichu yixue yu linchuang, 2020)
Objective To investigate the effect of abdominal paracentesis drainage (APD) on TLR4 expression in the liver of rats with early severe acute pancreatitis (SAP) and its significance. Methods The rats were randomly divided into sham operation group (sham group), SAP group(SAP model was established by retrograde injection of 5% sodium trasulfide cholate into the pancreatic bile duct) and SAP+APD group(drainage tube was placed and fixed on the basis of SAP). HE staining, automatic biochemical analyzer, ELISA, real-time PCR and Western blot were used to detect relevant indexes. Results Compared with sham group, the pathological injury of liver and pancreas were significantly worse and the pathological scores were significantly increased in the SAP group (P＜0.05), the activityies of serum amylase and lipase, serum indicators related to liver function, and serum levels of TNF-α, IL-1β were also significantly increased (P＜0.05); The mRNA and protein expressions of TLR4, the protein expression of NF-κB p65, TNF-α, IL-1β , and the phosphorylation levels of NF-κB p65 in liver tissues in the SAP group were significantly up-regulated than those in the sham group (P＜0.05); After APD intervention,the above indicators were significantly alleviated (P＜0.05). Conclusions Implementation of APD can significantly decrease the expression of TLR4 in liver tissue of rats with early SAP, inhibit the activation of downstream NF-κB signaling pathway, thus relieve the degree of liver injury.